Percutaneous Coronary Intervention in ST-Segment Elevation Myocardial Infarction: Late is Better Than Not Done at All - Cholid Tri Tjahjono; Sasmojo Widito; Budi Satrijo; Yoga Waranugraha; Muhammad Rizki Fadlan; Hendrawati Hendrawati; Mohammad Saifur Rohman (Universitas Brawijaya, 2020)
Background : For ST-segment elevation myocardial infarction (STEMI) patients, reperfusion through primary percutaneous coronary intervention (PCI) must be done to return the coronary arteries' blood flow. However, a large proportion of patients received late PCI. This study aimed to assess the impact of late PCI on the clinical outcomes of STEMI patients.Methods : A retrospective cohort study was conducted in Saiful Anwar General Hospital from January 2017 to April 2018. A total of 192 STEMI patients were divided into three groups: (1) on-time PCI; (2) late PCI; and (3) no PCI. The outcome measured included six months and 12 months of cardiovascular mortality and hospital readmission because of worsening heart failure and recurrent myocardial infarction (MI).Results: At six-month follow-up period, we found that hospital readmission was higher in the no PCI group (9.2% vs. 12.1% vs. 34.8%; p = 0.009). The recurrent MI (0% vs. 0% vs. 7.2%; p = 0.010) and worsening heart failure (6.2% vs. 8.6% vs. 33.3%; p < 0.001) was also higher in the no PCI group. On 12 months follow up period, the mortality (4.6% vs. 13.8% vs. 21.7%; p = 0.015) and hospital readmission (15.4% vs. 20.7% vs. 42%; p = 0.001) rate was higher in no PCI group. Hospital readmission because of worsening heart failure was also higher in no PCI group (9.2% vs. 17.2% vs. 37.7%; p = 0.015).Conclusion: Not performing revascularization was correlated with higher mortality and hospital readmission rate in STEMI patients. Late PCI was associated with better outcomes than not conducting revascularization.